Progress and Perspective of Professional Training in Medical Genetics and Genomics: A Report of the Association of Chinese Geneticists in America - Li, PhD, Peining; Zhang, MD, PhD, Hui Z.; Li, MD, Zhang, MD, PhD M.; Yu, MD, Chunli; Qi, PhD, Ming; Yu, MM, PhD, Jingwei; Wu, MM, PhD, Bai-Lin (North American Journal of Medicine and Science, 2013)
Medical genetics and genomics is a newly developed clinical specialty built upon accumulated knowledge of human genetics and discoveries of thousands of genetic disorders. Since 1991, medical genetics has been recognized as one of the 24 medical specialties and the American Board of Medical Genetics (ABMG) has organized training programs and provided certifications in clinical genetics, cytogenetics, molecular genetics and biochemical genetics. To publicize and promote this specialty, a task force on professional medical genetics training has been organized by members of the Association of Chinese Geneticists in America (ACGA). This report was written by the task force to outline the principle and practice of professional medical genetics training and review the progress and impacts of medical genetics and genomics in North America. For the past twenty years, the American College of Medical Genetics and Genomics (ACMG) has built a professionally trained work force and developed many policies, guidelines and standards governing clinical services and laboratory diagnostics. Educational programs to improve the knowledge and literacy on medical genetics for other health professionals and general public have been introduced. A comparison of the economic impact between basic genomic research and diagnostic genetic service showed similar impact multipliers in creating jobs and revenues. Genetic and genomic medicine is still in a stage of early development and rapid expansion but has been the driver for transforming ‘diagnostics/counseling’ based disease treatment toward ‘predictive/preventive’ oriented health maintenance. This report is aimed to introduce professional medical genetics training to qualified physicians and graduate students and also facilitate medical genetics specialty in China through professional consultation and exchange training programs. [N A J Med Sci. 2013;6(4):173-180. DOI: 10.7156/najms.2013.0604173]